Study of etiologies of postmenopausal bleeding by cytology and histopathological examination - Kumari, Amrapali; Bharti, Atima; Bala, Ritika; Kumari, Sweta (International Journal of Research in Medical Sciences, 2025)
Background: Postmenopausal bleeding (PMB) is a common gynecologic complaint with a wide range of benign and malignant etiologies. While atrophic changes are the most frequent benign causes, PMB may also be the earliest sign of gynecological malignancies such as cervical and endometrial cancer, particularly in low-resource settings where screening uptake is low. Aim lies to determine the etiologies of PMB using cytological and histopathological evaluation and identify the most common associated factors, particularly those indicating malignant potential. Methods: A hospital-based cross-sectional study was conducted at Rajendra institute of medical sciences (RIMS), Ranchi, from April 2021 to August 2022. A total of 76 postmenopausal women presenting with vaginal bleeding were included. Detailed histories, clinical examinations, pap smear, transvaginal ultrasonography (TVS), and endometrial or cervical biopsies were performed. Histopathological findings were considered the definitive diagnosis. Data were analyzed using SPSS version 23.0, and associations were tested using chi square test and odds ratios (ORs) with 95% confidence intervals (CIs); a p<0.05 was considered significant. Results: The most common age group affected was 51-60 years (47.4%). Histopathological diagnoses revealed cervical cancer in 30.3% of cases, followed by atrophic endometrium (23.7%), cervical intraepithelial neoplasia (CIN) (23.7%), endometrial hyperplasia (10.5%), and endometrial cancer (6.6%). A significant association was found between low socioeconomic status and cervical cancer (p=0.03, OR=4.33). Early childbirth (≤19 years) was significantly associated with CIN (p=0.03, OR=3.14). Parity of 0-4 was associated with endometrial hyperplasia (p=0.03). Pap smear results correlated well with histopathological findings in high-grade lesions and malignancies. Conclusions: Cervical cancer remains the leading malignant cause of PMB, especially among women of low socioeconomic background. Atrophy and endometrial hyperplasia are significant benign causes. Cytology and histopathological examination remain essential tools for evaluating PMB, particularly in resource-limited settings.